THU0001 Tertiary Lymphoid Organs in Takayasu Arteritis: Are Locally Matured B Cells Involved in The Pathogenesis?. (15th July 2016) - Galy, A.; Clement, M.; Bruneval, P.; Hyafil, F.; Papo, T.; Nicoletti, A.; Sacre, K.
Abstract : Background: Takayasu arteritis (TA) is a large vessel vasculitis involving the aorta and its major branches. T cell mediated autoimmunity is thought to play a major role in its pathogenesis while the role of B cells is still unclear. Objectives: To study the presence of tertiary lymphoid organs (TLOs) in the aortic wall of TA patients and analyzing if their presence could be associated with the activity of the disease. Methods: Hematoxylin and eosin–stained sections from aorta specimens from patients with TA were screened for tertiary lymphoid organs (TLOs). The presence of B cell aggregates (CD20), follicular dendritic cells (FDCs, CD21), and high endothelial venules (HEVs, PNAd) was investigated by immunohistochemistry. Immune cells from the adventitial layer of one patient were characterized by flow cytometry. Demographic, medical history, laboratory, imaging, treatment and follow up data were extracted from medical records. Results: Aorta specimens from Bentall procedures were available from 7 patients (five female, aged 22 to 57 years) with TA in whom surgery was performed between 2009 and 2014. Surgical treatment was performed at TA diagnosis (n=4) or at a median of 108 [84–156] months after TA diagnosis. Disease was active at surgery in four patients according to NIH score. B cell aggregates-TLOs containing HEVs were observed in the adventitia of all but one patient. Ectopic follicles containing FDCs were found in 5 patients and appeared associated with aortic FDG uptake assessed by PET. In addition, flow cytometry analysis confirmed the accumulation of memory/germinal center–like B cells in the adventitial layer and showed the presence of antigen-experienced T follicular helper cells (Tfh). Conclusions: Apparently functional ectopic lymphoid neogenesis takes place in the aortic wall of a subset of patients with TA. Our data suggest that the B cells play a key role in the pathogenesis of TA. Disclosure of Interest: None declared